Barriers to access in maternal healthcare services in the Northern Bangladesh - Banik, Bijoy Krishna (South East Asia Journal of Public Health, 2017)
Poor women, in both rural and urban areas in the northern region of Bangladesh, experience high maternal mortality rate (MMR), and compared to other regions, this group also has a low proportion of receiving antenatal care (ANC) and of births assisted by the skilled health personnel. One of the prime factors for this situation is the lack of the poor mothers access to maternal health care (MHC) services. Finding out physical, social and organisational access barriers to MHC services and exploring how these barriers caused three delays in healthcare seeking behaviour were therefore the main objectives of the paper. The study used both primary and secondary data to meet its objectives. The primary data was collected from October to December in 2010 interviewing 160 mothers who were pregnant or delivered at least one baby during the last ten years and the heads of seven relevant health centres, administering eight focus group discussions and observing the field. An assortment of articles, reports, theses and books were consulted in complementing and substantiating the argument. The study found social (early marriage, perception of pregnancy and childbirth, high financial cost) and organizational (lack of female health staff, lack of a guiding principle in the health sector, in/exclusion errors in benefit distribution, low quality services) barriers more acute than physical (distance and waiting time) barriers. As concluded, all these barriers seem to have caused delays in seeking healthcare, reaching facility centres at the right time and receiving adequate services. The findings of the current study suggest that rescheduling official time of the service centre, recruiting and posting female health workers, following a guiding path and providing emergency obstetric care at free of costs are the feasible ways of getting better maternal health situation in the study areas. South East Asia Journal of Public Health Vol.6(2) 2016: 23-36